Mawazo Institute 2021 COVID-19 Follow-Up Survey Report - The Mawazo Institute (My University, 2022)
This report draws on a survey conducted in 2021 by the Mawazo Institute, a nonprofit research institute based in Nairobi, Kenya. The survey aimed to determine the lasting impact of the COVID-19 pandemic on Africa's higher education and research sector in the year after lockdowns and restrictions first began, and thus to provide a more comprehensive follow up to an earlier Mawazo Institute survey conducted in 2020. Full findings, along with an interactive map displaying regional differences in key results, are available at https://mawazoinstitute.org/publications.
Keywords: Africa; Careers; Early-career; E-learning; Higher Education; Mawazo Institute; Research; STEM; Survey; Women; Work-life Balance